Modification of the atomic structure of liquid Al0.973Ni0.027 eutectic alloy by carbon nanotubes - Shtablavyi, I.; Kovalskyi, O.; Plechystyy, V.; Pashko, Yu.; Mudry, S. (Physics and Chemistry of Solid State, 2020)
The short-range order structure of the liquid Al0.973Ni0.027 eutectic alloy and eutectic based composites with carbon nanotubes containing 5, 10 and 15% was investigated. The changes of the main structure parameters (interatomic distances, coordination numbers, cluster sizes) was analyzed depending on the nanotubes content and temperature of the composites. As a result of the addition of carbon nanotubes, the atomic structure contracting of the liquid Al0.973Ni0.027 eutectic was revealed.